Unexpected radiation resistance of core/shell ceramic oxide nanoparticles. (December 2018) - Blair, S.J.; Muntifering, B.R.; Chan, R.O.; Barr, C.M.; Boyle, T.J.; Hattar, K.
Graphical abstract: Highlights: HfOx /SiOx core/shell structure demonstrates unprecedented stability to radiation/temperature. Core/shell nanoparticle appear to prevent sputtering and stores displacement defects and implanted He or diffusion out of the core/shell structure. Core/shell structure may show promise for future cancer therapy concepts and micro-electronics design for radiation environments. Abstract: This report presents HfOx /SiOx core/shell nanoparticles that withstand extensive bombardment from both high energy heavy ions and low energy light ions. In addition, these core/shell nanoparticles are stable to thermal annealing up to 800 °C. These results suggest that the core/shell structures may enhance nanoparticle radiation stability.